P2CTS-3D IC: An Efficient Placement Aware Partitioning and Clock Tree Synthesis in 3D-integrated Circuits - Nair, Radeep Krishna Radhakrishnan; Pothiraj, Sivakumar; Nagarajan, Rajini (Applied Science and Engineering Progress, 2020)
The three dimensional integration of electronic circuits (3D-ICs) is one of the most promising approaches to encounter eternally increasing demands of functionality, performance, and power consumption. However, there exist many challenges in the minimization of power dissipation, skew, latency, wirelength, and obstacle avoidance in 3D-ICs. To overcome the discussed problems, an efficient placement aware partitioning and synthesis by clock tree have been proposed in 3D-ICs. In the proposed framework, the first process begins with the partition of netlist into multiple layers using hybrid Chemical Reaction Optimization (CRO) and K-Medoid algorithm and the placement process has been executed using Grid Warping Technique (GWT). Then, the routing process has been performed using the Line Search (LS) algorithm. The clock tree synthesis process gets accomplished with a Density Sorting (DS) algorithm that considers multiple TSVs. Further, the Clock tree topology has been implemented using the algorithm of Merging with Defer and Embedding (DME) and the algorithm of Graph with Neighbor at the Nearest. Consequently, the buffering and the embedding processes have been carried out to measure the total power dissipation and timing parameters. The proposed work minimizes the skew value compared to the other existing methods like GAP, EP, and SEA and it also provides efficient clock tree synthesis with Defer Merging and Embedding (DME) and Nearest Neighbor Graph (NNG) algorithm based methods as well as it reduces the skew optimally. Finally, the performance of the proposed work has been evaluated and proved to be better by considering the following metrics such as wirelength, power, skew, latency, and area.